(untitled) (Jurnal Destinasi Pariwisata, 2026)
The purpose of this study was to identify the forms of collaboration or support Saloka Theme Park provides to MSMEs through published digital content and activities. Researchers used a qualitative descriptive method, conducting observations and interviews with managers, visitors, and MSMEs. This study found that Saloka Theme Park’s use of social media plays a crucial role in enhancing promotions, expanding market reach, and strengthening relationships with consumers. Through digital platforms such as Instagram, TikTok, and WhatsApp, businesses can attractively display products, communicate directly with customers, and introduce local potential to the wider community. These promotional activities not only increase MSME sales and revenue but also contribute to strengthening Saloka Theme Park’s image as a leading tourist destination that supports the creative economy and community empowerment. Furthermore, the collaboration between MSMEs and Saloka management demonstrates positive synergy in building a sustainable, inclusive, and highly competitive tourism ecosystem, thereby driving local economic growth around the tourist area